Attitudes Towards Fake News: A Systematic Literature Review - Helal Alkhateri, Shaikha Mohammed Ali; M.Subramaniam, Indra Devi; Jano, Zanariah; Al-Shami, Samer Ali Hussein (Webology Center, 2021)
The rise of social media has provided a means for the spread of fake news, factual false information that is used to further a financial, political or societal agenda. The response to fake news on social media can be from individual users, social media platform companies, or respective national governments. This systematic literature review was designed to determine whether there is commonality across cultures and nations as to fake news exposure, response to encountering fake news on social media, and attitudes towards mediating efforts. A total of five published journal articles were selected, each using quantitative methods and representing five distinct geographical areas. These articles formed the bases for a systematic literature review that answered the research questions concerned with attitudes towards the threat of fake news, responses to fake news encountered on social media platforms, and attitudes towards efforts to curb fake news, whether by individuals, social media platform companies, or governments. Results showed universal recognition of fake news as a potential or real threat, mixed results as to whether fake news is read or shared by respondents, and mixed results regarding which actor (people, companies or governments) should lead mitigation efforts. These results emphasize the cultural and societal differences that must be considered when investigating fake news, particularly with the intention to develop recommendations or guidelines for its reduction.